Aggregation and luminescence in carbonized polymer dots. Issue 2 (20th January 2022) - Kang, Chunyuan; Tao, Songyuan; Yang, Fan; Yang, Bai
Abstract: The aggregate luminescence behavior of organic luminescent materials has been studied extensively. As a new kind of luminescent nanomaterials, carbonized polymer dots (CPDs) not only inherit the stability and biocompatibility of carbon materials, but also possess the luminescence tunability, water solubility, and high photoluminescence quantum yield of organic luminescent materials, rendering them a strong candidate for the next generation of light‐emitting materials. Previously, people mainly understood its luminescence from the perspective of carbon materials, but some luminescence mechanisms are still unclear. In this review, we discuss the luminescence mechanism by referring to organic luminescent materials with emphasis on their aggregation behavior. Firstly, three representative aggregate luminescence phenomena of organic luminescent materials are briefly introduced. Chromophores present in CPDs are elaborated to further discuss the potential interactions between them, with emphasis on the role of crosslinked polymer networks. On this basis, some special luminescence phenomena of CPDs in the aggregate state are summarized, and relevant mechanisms are discussed in detail to consolidate relevant statements. Abstract : An overview of the chromophores and the unique CEE luminescence mechanism in CPDs, with an introduction to the aggregate luminescence (ACQ, AIE, CTE) of organic luminescent materials and a discussion on the luminescence mechanism of some special luminescent phenomena originated from the aggregation of CPDs.